Characterization of multiple-antibiotic-resistant Salmonella typhimurium strains: Molecular epidemiology of PER-1-producing isolates and evidence for nosocomial plasmid exchange by a clone - (:unkn) unknown (AMER SOC MICROBIOLOGY, 1996)
We characterized epidemiologic and genetic features of nosocomially originated multiple-antibiotic-resistant Salmonella typhimurium isolates from two hospitals. A total of 32 multiply resistant strains, isolated during a 28-month period, were studied. Four resistance phenotypes were distinguished on the basis of the results of disc diffusion tests. Group 1 was resistant to chloramphenicol, gentamicin, tobramycin, amikacin, and the newer cephalosporins because of the production of an extended-spectrum beta-lactamase (PER-1). Group 2 exhibited the same pattern plus resistance to sulfamethoxazole-trimethoprim (Sst). Except for Sxt resistance, dominant phenotypes of both groups were transferred on an identical plasmid, pSTI1 (81 MDa). Group 3 was resistant to ampicillin, chloramphenicol, gentamicin, tobramycin, and Sxt. This pattern was also transferred on an 81-MDa plasmid (pSTI2) which differed from pSTI1 on the basis of EcoRI and HindIII restriction fragments, Group 4 was resistant to ampicillin, chloramphenicol, and tetracycline, and a 74-MDa nonconjugative plasmid was detected. Restriction fragment length polymorphism of RNA-encoding DNA and arbitrarily primed PCR tests revealed that bacteria from groups 1, 2, and 3 were clonally related. Epidemiologic data also supported the clonal-dissemination hypothesis. We conclude that S. typhimurium isolates acquire and exchange multiple-resistance plasmids in hospital microflora.
Keywords: BETA-LACTAMASE; IDENTIFICATION; SEQUENCES; OUTBREAK